2022
DOI: 10.1073/pnas.2207201119
|View full text |Cite
|
Sign up to set email alerts
|

Superenhancer drives a tumor-specific splicing variant of MARCO to promote triple-negative breast cancer progression

Abstract: The transcription variation, leading to various forms of transcripts and protein diversity, remains largely unexplored in triple-negative breast cancers (TNBCs). Here, we presented a comprehensive analysis of RNA splicing in breast cancer to illustrate the biological function and clinical implications of tumor-specific transcripts (TSTs) arising from these splicing junctions. Aberrant RNA splicing or TSTs were frequently harbored in TNBC and were correlated with a poor outcome. We discovered a tumor-specific s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…for a long time to identify potential targets for the precision treatment of TNBC, extensive efforts have been dedicated to identifying potential targets for precise therapeutic interventions of TNBC management. In recent years, Chinese researchers have successfully created the world's largest genetic map of TNBC, which proposes stratified subtypes with potential therapeutic targets and guides precision treatment strategies with refractory metastatic TNBC [47][48][49]. In our study, we have preliminarily explored the efficacy and safety of this new combination regimen (Apa+ddTCb) in the neoadjuvant therapy of TNBC.…”
mentioning
confidence: 99%
“…for a long time to identify potential targets for the precision treatment of TNBC, extensive efforts have been dedicated to identifying potential targets for precise therapeutic interventions of TNBC management. In recent years, Chinese researchers have successfully created the world's largest genetic map of TNBC, which proposes stratified subtypes with potential therapeutic targets and guides precision treatment strategies with refractory metastatic TNBC [47][48][49]. In our study, we have preliminarily explored the efficacy and safety of this new combination regimen (Apa+ddTCb) in the neoadjuvant therapy of TNBC.…”
mentioning
confidence: 99%
“…Interestingly, we found that TST and TMB were mutually exclusive in cancer especially in driver genes, which is significant as mutation analysis is an established approach for identifying driver genes in cancer. Similar to LIN28B which has been validated to enhance cancer cell proliferation and tumorigenesis 14 , we have also identified a tumor-specific transcript produced by MARCO , namely MARCO-TST 13 . This transcript plays a crucial role as an oncogenic transcription factor and therapeutic target, inducing metabolic dysregulation and hypoxic microenvironment in triple-negative breast cancer 13 .…”
Section: Discussionmentioning
confidence: 68%
“…Existing studies have focused on specific types of splicing events associated with abnormal transcripts, such as 3’ UTR splicing driving tumorigenesis 10 and exonic splicing analysis revealing tumor-specific events 11 . Our previous works have identified hundreds of tumor-specific transcripts (TSTs) in patients with hepatocellular carcinoma 12 and triple-negative breast cancer 13 , and characterized the functional roles of LIN28B-TST 14 and MARCO-TST 13 . We anticipate that various forms of TSTs with aberrant splicing due to epigenetic abnormalities or post-transcriptional processing may commonly exist in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…After performing experiments on patient-derived organoids, Xiao et al, indicated that the sphingosine kinase 1 (SPHK1) inhibitors PF-543 and fingolimod showed significantly higher efficacy in luminal androgen receptor (LAR) positive TNBC [ 51 ]. Additionally, Yang et al, employed patient-derived organoids, and validated the hypothesis that TNBC tumors with macrophage receptor with collagenous structure–TST (MARCO-TST) expression are more sensitive to bromodomain and extra-terminal protein inhibitors [ 52 ], whereas Zhang et al, developed patient-derived organoid models from two TNBC patients and concluded that pharmacologic inhibition by the covalent CDK14 inhibitor FMF-04-159-2 results in both organoid size and number reduction, decreased cell proliferation, and apoptosis induction [ 53 ]. Altogether, these observations reveal the countless advantages that patient-derived TNBC organoids might offer as suitable in vitro study platforms for alternative and targeted therapy sensitivity testing.…”
Section: The Use Of Tnbc Organoids For Alternative and Targeted Thera...mentioning
confidence: 99%